PERAN GURU PAI DAN ORANG TUA DALAM MENCEGAH PENYALAHGUNAAN NARKOBA DI SMAN 1 BESUK - Zaini Gunawan; Abd hayyi (LPPM STAI Muhammadiyah Probolinggo, 2026)
The purpose of this study is to examine the role of Islamic Religious Education (PAI) teachers and parents in preventing drug abuse among high school students in Besuk District, Probolinggo Regency. This study uses a descriptive qualitative approach, obtaining data through observation, in-depth interviews, and documentation studies. The results of the study show that the role of Islamic Religious Education (PAI) teachers is important in integrating the values of Islamic teachings into learning about the dangers of drugs, making it effective in instilling moral awareness in students to maintain their health and avoid drug abuse. In addition, parental involvement through open communication and supervision of children's social interactions is also a key factor in preventing drug abuse. Although these prevention efforts have shown positive results, obstacles such as limited time, resources, and peer influence remain major challenges. The synergy between PAI teachers, families, and the school environment has proven to strengthen drug prevention. Therefore, this study suggests the need to strengthen collaboration between schools and families, as well as increase the capacity of PAI teachers in providing more interactive and religiously-based materials related to the dangers of drugs. The results of this study are expected to provide benefits in the form of strengthening more targeted drug prevention strategies for adolescents.